Electrical and photoluminescence properties of Sm3+ doped Na0.5La0.5Bi8-xSmxTi7O27 ceramics. Issue 2 (1st February 2018) - Wang, Pengbin; Jiang, Xiangping; Chen, Chao; Xia, Xiang; Jiang, Yalin; Li, Xiaohong; Chen, Yunjing; Fan, Gang
Abstract: In this study, Sm 3+ doped Na0.5 La0.5 Bi8- x Sm x Ti7 O27 (NBT-BITL- x Sm, x = 0, 0.01, 0.015, 0.02, and 0.03) ceramics were synthesized via a conventional solid-state reaction process. The structural, electrical, and photoluminescence properties of NBT-BITL- x Sm ceramics were systematically investigated. The crystal structure of NBT-BITL- x Sm was refined using XRD Rietveld refinement and found to possess a single orthorhombic structure at room temperature. Raman spectroscopy revealed that Sm 3+ ions preferred to substitute for Bi 3+ located in the A-sites of pseudo-perovskite layers, inducing a slight decrease in orthorhombic distortion. Strong characteristic emission peaks of Sm 3+ ions were observed in orange-red regions under a 407 nm laser source, and the sample with x = 0.015 achieved the optimal photoluminescent property. Dielectric measurements showed double anomaly permittivity peaks at the temperature of 589 and 600 ∘ C ( T m and T c, respectively). The complex impedance spectrum indicated that the electrical conductivities mainly originated from crystal grains at high temperature. The activation energy was calculated to be 1.37–1.44  e V from Arrhenius fitting results. After Sm 3+ substitution, the activation energy for conductivity was increased as a result of reduced oxygen vacancies.